FALSE POSITIVE RADIOIODINE POST-ABLATION SCAN IN SCALP REGION IN A WOMAN WHO USED HAIR COLORING REVEALED BY SPECT/CT - Manevska, Nevena; Stojanoski, Sinisha; Makazlieva, Tanja; Jovanovska, Anamarija (My University, 2019)
Radioiodine ablation with iodine-131 is a standard therapeutic procedure for patients diagnosed with differentiated thyroid carcinoma (DTC). We present a contamination artifact on whole-body scan (WBS), after radioiodine ablation due to papillary thyroid carcinoma. The hybrid imaging resolved the question of metastasis versus contamination.